Painful pachydermodactyly in a 39-year-old woman: A case report and review of the literature. (October 2021) - Hussain, Salman; Ehtesham, Maryam; Almas, Talal; Aldei, Ali
Abstract: We chronicle the case of a 39-year-old female who presented to the rheumatology clinic with a history of chronic, symmetrical polyarticular pain in her hands. Meticulous diagnostic workup to exclude ubiquitous culprit aetiologies, such as rheumatoid arthritis and psoriatic arthritis, was performed. A detailed clinical examination was performed and, coupled with the radiological imaging findings, divulged an underlying diagnosis of pachydermodactyly. The patient was commenced on etoricoxib to alleviate the pain, and was advised to avoid repetitive trauma to her hands. The present report delineates a unique case of painful pachydermodactyly, affecting both proximal interphalangeal joints as well as distal interphalangeal joints. To the best of our knowledge, this is the first case from the state of Kuwait. We further review the literature in order to better elucidate the varying clinical manifestations of an elusive and rare rheumatological condition. Highlights: Pachydermodactyly is a rare disease that can be easily misdiagnosed and treated as an inflammatory arthritis leading to the initiation of unnecessary systemic therapies. Pachydermodactyly follows a benign course, therefore aggressive therapy is typically not warranted. Pachydermodactyly presents a diagnostic challenge due to its ability to mimic several other etiologies that render the same physical finding of progressive proximal interphalangeal joint swelling.